The effectiveness The effectiveness of deep breathing relaxation and peppermint aromatherapy on post-cesarean pain - fira lakoro; Ahmad Safari Hidayat; Naurah Friza Shabira; Majid Nurrahman Amrin; Wahyuni Fatimah Zahra; Intan Mutiara Putri (Journal of Indonesian Anesthesiology Nursing, 2025)
Postoperative pain following cesarean section is a common complaint among mothers and can hinder the recovery process and reduce comfort. In addition to pharmacological therapy, nonpharmacological interventions such as deep breathing relaxation and peppermint aromatherapy are increasingly being used because they are relatively safe, easy to apply, and have minimal side effects. Evidence-based studies are needed to assess the effectiveness of both interventions in managing post-cesarean section pain. Methods: This study used a literature review method by examining eight relevant scientific journals. The journals reviewed were quantitative studies with various quasiexperimental designs that discussed the administration of deep breathing relaxation, peppermint aromatherapy, or a combination of both in post-cesarean section patients. Analysis was conducted by assessing changes in pain intensity before and after the intervention using validated pain measurement instruments, particularly the Numerical Rating Scale (NRS).